Erratum: CHUN-MEI HE, THI THANH HUONG NGUYEN & YI-HUA TONG (2025) Taxonomic notes on Pistacia cucphuongensis (Anacardiaceae) with its new distribution record in China. Phytotaxa 696 (1): 93–99. - He, Chunmei; Nguyen, Thi Thanh Huong; Tong, Yihua (Phytotaxa, 2025)
Erratum